2008
DOI: 10.2337/db07-1087
|View full text |Cite
|
Sign up to set email alerts
|

Pck1 Gene Silencing in the Liver Improves Glycemia Control, Insulin Sensitivity, and Dyslipidemia in db/db Mice

Abstract: OBJECTIVE-Cytosolic phosphoenolpyruvate carboxykinase (PEPCK-C; encoded by Pck1) catalyzes the first committed step in gluconeogenesis. Extensive evidence demonstrates a direct correlation between PEPCK-C activity and glycemia control. Therefore, we aimed to evaluate the metabolic impact and their underlying mechanisms of knocking down hepatic PEPCK-C in a type 2 diabetic model. RESEARCH DESIGN AND METHODS-PEPCK-C gene targeting was achieved using adenovirus-transduced RNAi. The study assessed several clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 46 publications
3
95
0
Order By: Relevance
“…In obese healthy subjects, hepatic ATP content was inversely related to BMI, decreasing steadily with increasing BMI (12). Hepatic knockdown of PEPCK, one of the key gluconeogenic enzymes, ameliorated hyperglycemia and insulin resistance with increased hepatic ATP content in db/db mice (13). Overall, all of these studies revealed that a decrease in ATP content is associated with an increase in glucose production in the livers of diabetic animals and humans.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…In obese healthy subjects, hepatic ATP content was inversely related to BMI, decreasing steadily with increasing BMI (12). Hepatic knockdown of PEPCK, one of the key gluconeogenic enzymes, ameliorated hyperglycemia and insulin resistance with increased hepatic ATP content in db/db mice (13). Overall, all of these studies revealed that a decrease in ATP content is associated with an increase in glucose production in the livers of diabetic animals and humans.…”
mentioning
confidence: 67%
“…These findings suggested that inhibition of hepatic glucose production would attenuate hyperglycemia and global insulin resistance in type 2 diabetic mice. Similarly, a previous report showed that silencing of hepatic PEPCK suppressed hepatic glucose production and improved global insulin resistance in db/db mice (13). In vitro, ATPSb overexpression increased intracellular and extracellular ATP levels in HepG2 cells and primary cultured mouse hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…PCK1 catalyzes the first committed step in gluconeogenesis, and its transcription is regulated by several transcription factors involved in nutrient and hormone signals, notably glucagon and glucocorticoids, and the opposing hormone insulin (8). Silencing of hepatic PCK1 in db/db mice improves their control of glycemia, insulin sensitivity, and dyslipidemia, consistent with the function of PCK1 in gluconeogenesis (9). In addition to these gluconeogenic enzymes, the WNT-signaling effector TCF7L2 was recently identified as a critical regulator of HGP and glucose homeostasis (10).…”
Section: Introductionmentioning
confidence: 82%
“…ACSL3 and ACSL4 are essential enzymes for fatty acid metabolism (32). PCK1, the rate-limiting enzyme for gluconeogenesis, and TCF7L2, the WNT signaling effector, are crucial for glucose metabolism, especially for HGP (9,10). Lipids or other inducers of insulin resistance stimulate the activation of PKCδ, PKCθ, and GSK3β, which phosphorylate IRS proteins on Ser residues, thereby attenuating insulin signaling (3,33,34).…”
Section: Alb-mir26amentioning
confidence: 99%
“…Because it is not possible to study this in intact cells because of the rapid metabolism of DG, we tested the ability of CETP to transfer DG in vitro. DG was incorporated into phosphatidylcholine/cholesterol liposomes and the effect of CETP on the transfer of DG to causes an equivalent decline in PCK protein ( 43 ), these data suggest that glycolysis, driven by glucose in the media, provides adequate glycerol 3-phosphate for this pathway under cell culture conditions.…”
Section: Dg As a Cetp Substratementioning
confidence: 88%